The comparable body: analogy and metaphor in Ancient Mesopotamian, Egyptian, and Greco-Roman medicien - Wee, John Z. (Studies in ancient medicine, 2017)
Front Matter -- Copyright page -- Acknowledgements -- List of Figures and Tables -- Abbreviations -- Transliteration Notes -- Periodization of Ancient Mesopotamia -- Contributors -- Introduction: To What May I Liken Metaphor? /John Z. Wee -- Analogy and Metaphor in Ancient Medicine and the Ancient Egyptian Conceptualisation of Heat in the Body* /Rune Nyord -- From Head to Toe: Listing the Body in Cuneiform Texts /M. Erica Couto-Ferreira -- The Stuff of Causation: Etiological Metaphor and Pathogenic Channeling in Babylonian Medicine1 /J. Cale Johnson -- Aristotle’s Heart and the Heartless Man /Lesley Dean-Jones -- Earthquake and Epilepsy: The Body Geologic in the Hippocratic Treatise On the Sacred Disease /John Z. Wee -- The Lineage of “Bloodlines”: Synecdoche, Metonymy, Medicine, and More /Paul T. Keyser -- Eye Metaphors, Analogies and Similes within Mesopotamian Magico-Medical Texts* /Strahil V. Panayotov -- The Experience and Description of Pain in Aelius Aristides’ Hieroi Logoi /Janet Downie -- Concepts of the Female Body in Mesopotamian Gynecological Texts /Ulrike Steinert -- Pure Life: The Limits of the Vegetal Analogy in the Hippocratics and Galen /Brooke Holmes -- Animal, Vegetable, Metaphor: Plotinus’s Liver and the Roots of Biological Identity /Courtney Ann Roby.
Keywords: Konferenzschrift -- 2014 -- Chicago, Ill.; Metapher; Medizin; Antike; Mesopotamien